When practitioners and scientists collide : an evidence-based activity for management education - Hartman, Kevin (2020)
In this quasi-experimental study, our team of management educators and learning scientists tested an evidence-based learning activity designed to have students internalize the importance of empathy. 83 students enrolled in two sections of a second-year undergraduate management course completed a version of a voluntary online activity. Prior to the activity, students in one section of the course received materials highlighting the core functions of management (planning, organizing, leading and controlling). Students in the second section of the course received materials introducing the design thinking process. To help students internalize the value of empathy, we incorporated design principles from cognitive, educational, and social psychology into the activity. At the end of the activity, students applied their set of resources to help a prospective student solve an ambiguous management problem. Students in the functions of management condition overwhelmingly focused on the outcome of the issue, while students in the design thinking condition were more likely to focus on the process that would lead to the outcome. Students in the design thinking condition were also significantly more likely to display evidence of cognitive empathy for the prospective student.